2014
DOI: 10.7860/jcdr/2014/7745.4403
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Various Tests for Diagnosis of Concurrent Malaria and Typhoid Fever in a Tertiary Care Hospital of Northern India

Abstract: The interpretation of Widal test and Malaria card test, when diagnosing concurrent malaria and typhoid fever, must therefore be done with a lot of caution. Negative or positive Widal agglutination test is neither definitive nor completely informative. Similarly erroneous interpretation of Malaria card test (especially Antibody detection card test) result may lead to prolonged treatment and economic burden on patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
4
10
2
Order By: Relevance
“…In a similar study conducted in 2014, a co-infection rate of 1.6% for malaria and typhoid was observed. 8 Furthermore, a co-infection rate of 6.7% (20/300) was observed in our study using Widal test for typhoid and peripheral blood smear for malaria. A study from Ethiopia reported coinfection rate of 6.5% using Widal test and 0.5% with blood culture, which is in accordance to our study.…”
Section: Discussionsupporting
confidence: 47%
“…In a similar study conducted in 2014, a co-infection rate of 1.6% for malaria and typhoid was observed. 8 Furthermore, a co-infection rate of 6.7% (20/300) was observed in our study using Widal test for typhoid and peripheral blood smear for malaria. A study from Ethiopia reported coinfection rate of 6.5% using Widal test and 0.5% with blood culture, which is in accordance to our study.…”
Section: Discussionsupporting
confidence: 47%
“…There is high prevalence of typhoid fever from Widal test when compared to stool culture according to the present study. This finding was in conformity with the findings of Wam et al, [18]; Gemechu et al, [19] and Verma et al, [20]. The high Widal prevalence in the present study could be associated with cross-reacting antibodies from febrile patients other than typhoid fever [18].…”
Section: Discussionsupporting
confidence: 94%
“…The result is lower than that of Gemechu et al, [19], which showed a high prevalence of typhoid fever (20%) using stool culture and 68.4% using Widal test method in Ethiopia. On the other hand, this result is lower than that of Verma et al, [20] in Northern India who found prevalence rate of 10.8% and 3.3% for Widal test and stool culture respectively. Low prevalence rate of typhoid fever among febrile patients in this study is attributed to high malaria prevalence in the area.…”
Section: Discussioncontrasting
confidence: 76%
“…Our results were in concordance with those of the studies which were reported by some researchers in other endemic states of India. [24][25][26][27] For the anti-TH antibodies, an agglutinin titre of up-to 1:60 was discovered in the apparently healthy study population, whereas for the anti-TO antibodies, our result was lower (a titre of 1:40), which was in contrast to the reports of some other workers but it was in accordance with the reports of some previous studies. Several factors may have contributed to this discrepancy, because the differences in the antibody response may be due to the poorly standardized antigen preparation and the sharing of the antigen determinants with other Salmonellae.…”
Section: Discussionsupporting
confidence: 91%